Counterintuitive anisotropy of electron transport properties in KC 60(THF)5×2 THF fulleride - Kromer, A.; Wedig, Ulrich; Roduner, E.; Jansen, M.; Amsharov, Konstantin (Angewandte Chemie International Edition, 2013)
Spin and charge transport: The electronic and structural properties obtained from KC60(THF)5×2 THF single crystals are reported (see picture). An important finding is the presence of one-dimensional electric conductivity and the observation of counterintuitive anisotropy for electron transport. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: conductivity; density functional calculations; fullerenes; X-ray diffraction